WEAR ANALYSIS ON BACKFLANGE LRT BECAUSE OF USE OF RESTRAINING RAIL - Pradana Nugroho, Aditya
Train users in Indonesia from 2006 to 2018 continue to increase, especially in users of the commuter train or transit system. The LRT transit system has characteristics, including the use of a small curve radius to access densely urban areas. A safety device in the form of a restraining rail must be installed in a curve with a small radius to avoid any derailment. However, non-optimal installation of the restraininf rails can cause wear on the backflange wheel. The research in this undergraduate assignment aims to optimize the parameters of railroad and restraining rails so that the wear on the backflange wheel is reduced but still functions as a safety tool against derailments. To fulfill this research, a dynamic model of the LRT with restraining rail using Universal Mechanism software has been built. The restraining rail is modeled by modifying the rail profile curve of the main rail and through the analysis of the wheel profile pair with the rails it can be identified the contact point between the wheel tread and the main rail and the backflange wheel with the forced rail. The dynamic model of the LRT with forced rail is then validated by comparing the forces at the contact point of the restraining rail while passing a constant radius curve between the analytical calculations and the simulation results of UM Simulation. The validation results show a difference of 1% so that the model can be considered representative. Furthermore, testing is carried out at a curve radius of 80 m with several rail road parameters using the dynamic model. The test simulation results show that the flangeway width of 60 mm produces a fairly high wear index. The most optimal flangeway width ranges from 68 mm to 70 mm. Other optimal parameters that reduce the wear index are a cant height of 50 mm, a rail widening of 20 mm, and an operating speed of 20 km/h. Another alternative to lowering the wear index on the rear wheel flange is to lubricate the restraining rail.